Elementary Chinese I - Zhou, Wenying (Open textbook library., 2022)
This open textbook is designed for beginners learning Chinese as a second/foreign language. This book aims to introduce learners to standard Chinese pronunciation, character knowledge, basic conversational phrases, grammar and vocabulary use, and cultural knowledge. Throughout the eight chapters, learners will explore: greetings and self-introduction, hobbies, nationalities, family members and occupations, inviting friends to dinner, talking about food and beverage, making phone calls, and talking about classes and exams. Learning activities include audio recordings so students can listen to the pronunciation of vocabulary words and observe dialogue between speakers. The book also includes videos with captions, allowing learners to listen, watch, and read. Original interactive activities have been created by the author to facilitate the practice of target vocabulary and dialogues.